Healthcare professionals' experiences of reviewers' conduct during incident reviews at public hospitals in Gauteng, South Africa. (2021) - Nkosi, Elizabeth Malefu; Armstrong, Sue; Nkosi-Mafutha, Nokuthula
Abstract: Purpose: To gain an understanding of the healthcare professionals' experiences of the reviewers conduct during incident reviews at specific public hospitals in Gauteng, South Africa. Background: Incident reviews are undertaken as quality improvement initiatives in healthcare settings. These reviews consist of a panel of dedicated team of reviewers who schedule a session to determine the sequence of events following an adverse event, identifying nursing care and system problems, the factors that contributed, make recommendations and create plans towards amendments. Methods: A qualitative, descriptive, phenomenological, and contextual research design was used. Twelve professional nurses and one medical doctor with psychiatrist qualifications from the public hospitals were purposively selected. Data were collected by means of semi-structured interviews which were digitally recorded and transcribed verbatim. Data was analysed using thematic analysis according to Braun and Clarke (2006). Results: The reviewers conduct were negatively experienced before, during and after the reviews. The participants highlighted that reviewer empathy, which is non-judgmental and non-punitive during the reviewing process was imperative to create learning opportunities and prevent further adverse events. Conclusion: A confrontational insensitive review session promoted the repeat of adverse events and a decline in quality nursing care. The findings provided a foundation for recommendation for reviewer empathy, sensitivity, a positive and professional conduct during the conduct of reviews.